The Use of Carotene Materials as the Source of Red Color Pigmentation on Leopard Grouper Larvae (Plectropomus leopardus) - Kusumawati, Daniar; Setiawati, Ketut Maha (Aquacultura Indonesiana, 2016)
Carotenoid is one of nutrition factors which can improve red color pigmentation. The purpose of this study was to investigate the best type of carotene which can increase red pigment performance and to evaluate how long the effect should be retaining in order to maintain red color performance on leopard grouper seeds. This study consisted of 2 experiments; those were the effect of various kinds of carotene materials in feed addition and the effect of the termination of the addition of carotene materials in the feed toward red color performance on leopard grouper  seed. The treatments given to the first experiment were the provision of various kinds of carotene materials which were type of A. Haematococcus pluvialis, B. Phaffiarhodozyma, C. Astax Oil, D. Control (without carotene materials) and the treatments to the second experiment are A. Leopard grouper  seed – phaffia was still given additional Phaffia rodhozyma, B. Leopard grouper  seed – haematococcus was still given additional Haematococcus pluvialis, C. leopard grouper seed (from larvae - phaffia / haematococcus) was terminated from carotene materials addition. The first experiment was applied from larva up to D60 seed and for the second experiment was the follow-up response from the first experiment conducted on D60 seed up to D150. Based on the study result, it indicates that carotene materials of Haematococcus pluvialis type gave the best color performance improvement (P value 4.71 x 10-7 < 0.05). The provision of carotene materials intake decreases color performance both visually and total contain of carotene (P value 5.97 x 10-5< 0.05) (Tabel 1). Carotenenoids should be continuously given as trigger to maintain red color performance on leopard grouper  seed. There was protein band in the range of 82.1 – 84.2 kDa which was assumed as protein expression of astaxanthin